Stock Value Analysis Using Absolute Valuation and Relative Valuation Approaches - Jaunanda, Meiliana (Universitas Pelita Harapan, 2023)
The world of investment in Indonesia has been growing from year to year. This can be seen from the IHSG, which has been rising every year, accompanied by the improving economic growth in various sectors. One of the sectors that plays an important role in the development of the country is the manufacturing sector. The manufacturing sector has a high capitalization value and is quite dominant in Indonesia and abroad. This has attracted the attention of investors to invest their capital. However, before buying and selling a stock, investors first analyze whether the stock they are investing in is overvalued, fairvalued, or undervalued. This study uses the absolute and relative valuation technique to assess stocks using the proxies of Price book value (PBV) and Price earning ratio (PER) and determine whether the stock is overvalued, fairvalued, or undervalued. Sampling was done on manufacturing companies that have consistently distributed dividends during the period 2017-2021. The results of the study are that the shares that were undervalued were CLPI and INDS. In 2018, the shares that were undervalued were CLPI, TOTO, and WTON. In 2019, the shares that are undervalued are ALDO, CLPI, TSPC, and WTON. In 2020, the shares that are undervalued are CLPI, INDF, and TOTO and in 2020, the shares that are undervalued are CLPI, INDF, INDS, and TSPC and only CLPI, INDS shares from 2017-2021 are in an undervalued position and WTON shares in 2021.